Flash point prediction for the binary mixture of phosphatic solvents and n-dodecane from UNIFAC group contribution model. (January 2015) - Balasubramonian, S.; Srivastav, Ravi Kant; Kumar, Shekhar; Sivakumar, D.; Sampath, M.; Kamachi Mudali, U.; Natarajan, R.
Abstract: The flash point temperature of Tri- n -butyl phosphate(TBP) and Tri-iso-amyl phosphate(TiAP) in n -dodecane binary mixture has been measured for the entire concentration range using the continuously closed cup flash point apparatus based on the ASTM D6450 method. The flash point was predicted using the UNIFAC group contribution model. The measured flash point was also compared with the prediction from the NRTL, UNIQUAC and Ideal solution models. The UNIFAC model is able to predict the flash point fairly well for the TBP–dodecane mixture and for TiAP–dodecane mixture no improvements is obtained over the ideal solution assumption. The flash point shows positive deviation from ideal solution behavior for both the binary mixture.